A Descriptive Study On Teaching Reading Method To The Eight Grade At SMP Negeri 3 Randudongkal In 2013/ 2014 Academic Year - Puspanggara, Galih; , Dr. Dwi Haryanti, M.Hum; , Drs. Djoko Srijono, M.Hum (2014)
This research is to describe the teaching reading conducted by teacher to the eighth grade of SMP Negeri 3 Randudongkal in 2013/2014 academic year. It is conducted to know how the teaching reading implemented by teacher and the problem faced by them during teaching-learning process. The research is a descriptive research. The writer collets the data by observing teaching-learning process, conducting the interview, and documenting some important data that support to this research. The data are from interview script, field note, syllabus, text book, and lesson plan. The methods of collecting data are conducting observation, interview, and analyzing document. The techniques of analyzing data are reduction the data, data analysis, display the data, and conclusion and verification. The results of the research are the method on teaching reading used by teacher are GTM and GBA, the goal of teaching reading is to help the students in understanding the reading material such as genre text, reading materials that are given to the students are recount text, narrative text, and procedure text, teaching-learning process is implemented by using three phase technique: prereading, whilst-reading, and post-reading, teaching media used by teacher from "Let's Talk", copied texts taken from internet, English dictionary, and white board, teaching evaluation is giving the exercise such answering question related the material by written or oral, students' assignment, and making text independently. Type of the exercise is the multiple choice and essay, problems faced by teacher are inability to conditioning the class, limited vocabulary by students, limited media, and the methods used by teacher.